BIBLICAL INTERPRETATION, MYTHOLOGY, AND A THEORY OF ETHNIC VIOLENCE - Hamerton-Kelly, Robert (Scriptura, 1994)
Aristotle might have been optimistic when he said that human beings by nature desire to understand, nevertheless, understanding is the professional obligation of the intellectual, and since there can be no understanding without theory, we intellectuals, cannot neglect the search for theory, Violence is an odd thing to want to understand, but we seek to understand it not to enhance the pleasure of contemplation, but rather to deal with it more effectively. Therefore, we seek a theory of violence to use as a lens through which to view the evidence. I wish to propose such a theory as a contribution to the discussion of the possible role theology might play in an understanding of the violence that attends the birth of the new South Africa. As an outside observer I cannot understand the situation as well as those who are existentially involved and so I must present the theory in general terms and leave it to others to decide its applicability.